The Collective Value of "Me" (and it's Limitations): Towards a More Nuanced Understanding of Individual and Collective Coping with Prejudice. (September 2015) - Becker, Julia C.; Barreto, Manuela; Kahn, Kimberly B.; de Oliveira Laux, Stephanie H.; Stroebe, Katherine; de Lemus, Soledad
<x xml:space="preserve">Abstract</x> Within the social identity tradition, individual and collective responses to social disadvantage are typically seen as mutually exclusive. This study (N = 120) provides a more nuanced understanding of individual and collective responses to social disadvantage by examining the ways in which women anticipate responding to "daily sexism." We test how responses are independently related to ingroup identification, disidentification, and perceived ingroup homogeneity. Results show that women favor confronting sexism over inaction, even if that involves disparaging the ingroup. Specifically, women expect to engage in both individual and collective strategies in response to a sexist statement. Identification with women was positively associated with both collective and individual (nongroup disparaging) responses, but only collective responses related to broader intentions to engage in collective action for social change. Finally, perceived group homogeneity uniquely increased agreement with the sexist statement, endorsement of inaction, and group‐disparaging responses. Theoretical and practical implications are discussed.